Gender-Based Double Standard in Taylor Swift's Song - Siregar, Lita Amanah; Ulfa, Maria (Universitas Dian Nuswantoro, 2022)
This research examines the way gender based double standards represented in Taylor Swift’s song namely “The Man”. The objects of the research are the song lyrics and music video of Taylor Swift’s “The Man”. The research applies social semiotic analysis theoretical framework. The song lyric is analysed using the ideational metafunction of Halliday, while the music video using the representational meaning of Kress and Leeuwen’s Visual Grammar. The result shows that, in the lyrics, the portrayals of gender-based double standards mostly realized through the use of relational and material processes. The relational processes relates man with attributes such as “more of a boss”, “fearless leader”, “alpha type”, and “Leo”(Leonardo Di Caprio), while the material actualizes man’s action such as “play the field”, “hustled” and “put in the work”. Additionally, the Music Video is dominated by reactional processes that reveal people’s positive reaction towards man’s action and followed by symbolic attribute process that represents men in a more central, active and agentive manner and women in a marginal, passive, and object positions. Man is also portrayed as successful leader, greatest dad, rich man, while women are mostly seen laying down, wearing sexy attire and as object’s to man’s pleasure.